Early Land Plants Today: Taxonomy, systematics and nomenclature of Gymnomitriaceae - Vana, J.; Soderstrom, L.; Hagborg, A.; Von Konrat, M.; Engel, J. J. (Phytotaxa, 2014)
There remains a critical need to synthesize the vast amount of nomenclatural, taxonomical and global distributional data for liverworts. This is fundamental in taxonomists’ efforts towards developing a working list of all known plant species under the auspices of the Convention on Biological Diversity (CBD) as well as having far reaching implications and applications, including providing a valuable tool for taxonomists and systematists. We here provide the first synthesis of the taxonomy, systematics, and nomenclature of the family Gymnomitriaceae. The family is here conservatively treated to include ten genera representing 73 accepted species. We propose 149 new synonyms, 102 of them for validly published names. Significantly, we briefly discuss recent developments based on molecular studies and we predict future investigations will dramatically redefine the family. Detailed taxonomy and nomenclature is treated for almost 800 names associated with the family. Noteworthy remarks on various aspects of the distribution, ecology, conservation, and biology of members of the family are also included.